Model Pendidikan Karakter Berbasis Islam: Solusi Menghadapi Krisis Moral Di Era Global - Avicni Miramadhani; Eko Nursalim (Jurnal Kajian Islam dan Sosial Keagamaan, 2024)
The era of globalization has brought about a significant moral crisis in the younger generation, characterized by increasing individualism, materialism, and immoral behavior. This research discusses an Islamic-based character education model as a solution to these challenges. Using a qualitative approach through a literature study, this research explores the concept of Islamic values, such as faith, taqwa, honesty, trustworthiness, justice, and ihsan, which are relevant in shaping individual character. It also offers implementation strategies, such as integration of Islamic values in the curriculum, habituation of Islamic behavior, and collaboration between schools, families, and communities. Despite facing challenges such as limited teacher understanding and the influence of global culture, this research provides recommendations for solutions through training, media literacy, and technology utilization. The findings are expected to be a practical guide to improving the morality of the younger generation in the modern context.